Power output during stage racing in professional road cycling - Vogt, S.; Heinrich, L.; Schumacher, Y. O.; Blum, A.; Roecker, K.; Dickhuth, H. H.; Schmid, A. (Medicine & Science in Sports & Exercise, 2006)
Purpose: The aim of the study was to evaluate the power output during a multistage professional road race using direct power measurements and to compare these results with the performance measurements using competition heart rate recordings.